Enhanced optical gain clamping for upstream packet based trafﬁc on hybrid WDM/TDM-PON using ﬁber bragg grating - Neto, B. (2012)
In this paper, we propose a method to mitigate the temporal power transients arising from Erbium doped ﬁber ampliﬁers (EDFAs) on packeted/bursty scenario. The technique, applicable on hybrid WDM/TDM-PON for extended reach, is based on a low power clamping provided by a distributed feedback (DFB) laser and a ﬁber Bragg grating (FBG). An mprovement in the data signal Q factor was achieved keeping the clamping control signal with a low power, accompanied by a maximum reduction in the gain excursion of 1.12 dB